PERAN CELEBRITY ENDORSER DALAM MEMPENGARUHI KEPUTUSAN PEMBELIAN GEN Z PENGGUNA INSTAGRAM PADA PRODUK EMINA COSMETICS - Aprilani, Deddy; Putri, Mutiara Dwi Reza; Nugeraha, Prasetya (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2025)
This study aims to determine the effect of celebrity endorser s on the purchasing decisions of Gen Z Instagram users on Emina Cosmetics products. Celebrity endorser s in this study were analyzed using the TEARS indicator which consists of Trustworthiness, Expertise, Attractiveness, Respect, and Similarity. This study uses a quantitative approach with a causal explanatory method. The data collection technique was carried out through distributing questionnaires to 100 respondents who are Instagram users from Gen Z who know or have seen Emina Cosmetics promotions by celebrity endorser s. Data analysis was carried out using validity, reliability, descriptive analysis, classical assumption test, simple linear regression, t test, and coefficient of determination. The results showed that celebrity endorser s had a significant and positive effect on purchasing decisions with a significance value of 0.000 <0.05 and a regression coefficient of 0.133. The coefficient of determination (R²) of 0.355 indicates that 35.5% of purchasing decisions are influenced by celebrity endorser s, while the rest is influenced by other factors outside this study. Thus, the use of celebrity endorser s that are in accordance with the characteristics of the target market can be an effective strategy in increasing consumer purchasing decisions, especially in generation Z.